Brachial plexus birth injury and cerebral palsy lead to a common contracture phenotype characterized by reduced functional muscle length and strength - Nikolaou, Sia; Garcia, Micah C.; Long, Jason T.; Allgier, Allison J.; Goh, Qingnian; Cornwall, Roger (Frontiers in Rehabilitation Sciences, 2022)
Introduction: Brachial plexus birth injury (BPBI) and cerebral palsy (CP) both cause disabling contractures for which no curative treatments exist, largely because contracture pathophysiology is incompletely understood. The distinct neurologic nature of BPBI and CP suggest different potential contracture etiologies, although imbalanced muscle strength and insufficient muscle length have been variably implicated. The current study directly compares the muscle phenotype of elbow flexion contractures in human subjects with BPBI and CP to test the hypothesis that both conditions cause contractures characterized by a deficit in muscle length rather than an excess in muscle strength. Methods: Subjects over 6 years of age with unilateral BPBI or hemiplegic CP, and with elbow flexion contractures greater than 10 degrees on the affected side, underwent bilateral elbow flexion isokinetic strength testing to identify peak torque and impulse, or area under the torque-angle curve. Subjects then underwent needle microendoscopic sarcomere length measurement of bilateral biceps brachii muscles at symmetric joint angles. Results: In five subjects with unilateral BPBI and five with hemiplegic CP, peak torque and impulse were significantly lower on the affected versus unaffected sides, with no differences between BPBI and CP subjects in the percent reduction of either strength measurement. In both BPBI and CP, the percent reduction of impulse was significantly greater than that of peak torque, consistent with functionally shorter muscles. Similarly, in both conditions, affected muscles had significantly longer sarcomeres than unaffected muscles at symmetric joint angles, indicating fewer sarcomeres in series, with no differences between BPBI and CP subjects in relative sarcomere overstretch. Discussion: The current study reveals a common phenotype of muscle contracture in BPBI and CP, with contractures in both conditions characterized by a similar deficit in muscle length rather than an excess in muscle strength. These findings support contracture treatments that lengthen rather than weaken affected muscles. Moreover, the discovery of a common contracture phenotype between CP and BPBI challenges the presumed dichotomy between upper and lower motor neuron lesions in contracture pathogenesis, instead revealing the broader concept of “myobrevopathy”, or disorder of short muscle, warranting increased investigation into the poorly understood mechanisms regulating muscle length.